The tragedy of conservation - Raymond A. Rogers (Canadian Science Publishing, 2021)
A central contention of this paper is that conservation strategies are failing because they have become increasingly integrated into, and share the assumptions of, the structures of capitalism. As a result, conservation is becoming a strategic specialty within capitalism, rather than an ethical challenge to its basic assumptions. The paper examines this integration by analysing the way Hardin's argument in the "tragedy of the commons" metaphor was taken up by policy makers in Canada's East Coast fishery and a case is made that, as seen in the case of the fishery, this strategic integration limited the analytical capability of conservation to highlight the causes of environmental degradation. The critical literature on Hardin's model points to the failure to recognize the importance of social relations and local institutional arrangements in combatting environmental failure. This paper contributes to the importance of "the social" in conservation debates by emphasizing Polanyi's contrasting definitions of formal and substantive economics and the way they relate to contrasting conceptions of tragedy, as set out by Hardin (formal tragedy from above) and Goldmann's conception of a historically specific tragedy that can be described as substantive tragedy from below. The analytical failure associated with Hardin's metaphor can serve as a cautionary tale for current strategic and specific conservation strategies that tend to downplay the importance of ethical and social issues.